PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan JNE di Kota Semarang) - Mohammad Rifki Arif Wicaksana; Suryono Budi Santosa (Diponegoro Journal of Management, 2022)
Within the freight forwarding industry, many new competitors have sprung up and more and more choices of freight forwarding services are available. Currently there are many expedition services with unique features and characteristics to meet the needs of shipping goods. One of these expedition services is PT JNE, a company engaged in distributing or shipping goods. In line with this, the rapid development of science and technology and information also affects changes in human behavior. In the end, consumers have a tendency to choose products to be consumed and which are not so that a consumer satisfaction arises, which has an impact on the interest in reuse. This research aims to determine the influence that arises through product quality, service quality, perceived price, and consumer satisfaction to foster repurchase intention of PT. JNE. The data collection method used in this study is purposive sampling. Then this study was tested with a total of 125 samples obtained from questionnaires and specifically led to customers who had used JNE expedition services in Semarang City. The data obtained is processed using SEM analysis with the help of AMOS software to test 4 hypotheses. The results of this study showed that product quality, service quality, perceived price, and consumer satisfaction have a positive and significant effect on repurchase intention.